The Strategy of Ontological Negativity in Meister Eckhart’s Metaphysics and in Philosophical Traditions of India - Tatyana Lifintseva; Dmitry Tourko (Religions, 2018)
In this article, the authors investigate ontological strategies in Meister Eckhart’s metaphysics, which remounts Neoplatonism and the Corpus Areopagiticum, and in two schools of Indian philosophical tradition, the Advaita Vedanta and Early Buddhism. Along with differences in the anthropology, epistemology, and soteriology of these traditions, we can find similar strategies of ontological negativity and mystical experience in both traditions: detachment from the world of images and forms as the highest blessing; non-association of oneself with corporality, feelings, cognitive ability and reason; interiorizing the intentionality of consciousness, and termination of its representative function. Practically all systems of Indian philosophy were projects of liberation or personal transformation from subjugation and suffering into being free and blissful. The idea of spiritual release is also the cornerstone of Christian salvation as with the renouncement of sin and entering blissful unity with God. The apophatic doctrine of Christian neo-platonic mystics about the concealment, non-comprehensiveness, and inexpressibleness of God as the One and Nothingness, and also the idea of comprehension of God by means of detachment from the created world and one’s own ego, gives us the opportunity for such comparative analysis.